Lower cost strategies for triage of human papillomavirus DNA‐positive women. Issue 12 (3rd December 2013) - Qiao, You‐Lin; Jeronimo, Jose; Zhao, Fang‐Hui; Schweizer, Johannes; Chen, Wen; Valdez, Melissa; Lu, Peter; Zhang, Xun; Kang, Le‐Ni; Bansil, Pooja; Paul, Proma; Mahoney, Charles; et al.
<x xml:space="preserve">Abstract</x> Using human papillomavirus (HPV) testing for cervical cancer screening in lower‐resource settings (LRS) will result in a significant number of screen‐positive women. This analysis compares different triage strategies for detecting cervical precancer and cancer among HPV‐positive women in LRS. This was a population‐based study of women aged 25–65 years living in China (n = 7, 541). Each woman provided a self‐collected and two clinician‐collected specimens. The self‐collected and one clinician‐collected specimen were tested by two HPV DNA tests—careHPV™ and Hybrid Capture 2; the other clinician‐collected specimen was tested for HPV16/18/45 E6 protein. CareHPV™‐positive specimens were tested for HPV16/18/45 DNA. HPV DNA‐positive women underwent visual inspection with acetic acid (VIA) and then colposcopic evaluation with biopsies. The performance for detection of cervical intraepithelial neoplasia grade 3 or cancer (CIN3+) among HPV DNA‐positive women was assessed for different triage strategies: HPV16/18/45 E6 or DNA detection, VIA, colposcopic impression, or higher signal strength (≥10 relative light units/positive control [rlu/pc]). The percent triage positive ranges were 14.8–17.4% for VIA, 17.8–20.9% for an abnormal colposcopic impression; 7.9–10.5% for HPV16/18/45 E6; 23.4–28.4% for HPV16/18/45 DNA; and 48.0–62.6% for higher signal strength (≥10 rlu/pc), depending on the HPV test/specimen combination. The positivity for all triage tests increased with severity of diagnosis. HPV16/18/45 DNA detection was approximately 70% sensitive and had positive predictive values (PPV) of approximately 25% for CIN3+. HPV16/18/45 E6 detection was approximately 50% sensitive with a PPV of nearly 50% for CIN3+. Different triage strategies for HPV DNA‐positive women provide important tradeoffs in colposcopy or treatment referral percentages and sensitivity for prevalent CIN3+.